The effect of functional hearing loss and age on long- and short-term visuospatial memory: evidence from the UK biobank resource - Rönnberg, Jerker; Hygge, Staffan; Keidser, Gitte; Rudner, Mary (Frontiers in Aging Neuroscience, 2014)
The UK Biobank offers cross-sectional epidemiological data collected on > 500 000 individuals in the UK between 40 and 70 years of age. Using the UK Biobank data, the aim of this study was to investigate the effects of functional hearing loss and hearing aid usage on visuospatial memory function. This selection of variables resulted in a sub-sample of 138 098 participants after discarding extreme values. A digit triplets functional hearing test was used to divide the participants into three groups: poor, insufficient and normal hearers. We found negative relationships between functional hearing loss and both visuospatial working memory (i.e., a card pair matching task) and visuospatial, episodic long-term memory (i.e., a prospective memory task), with the strongest association for episodic long-term memory. The use of hearing aids showed a small positive effect for working memory performance for the poor hearers, but did not have any influence on episodic long-term memory. Age also showed strong main effects for both memory tasks and interacted with gender and education for the long-term memory task. Broader theoretical implications based on a memory systems approach will be discussed and compared to theoretical alternatives.